GranDIHC-BR: Grand Research Challenges in Human-Computer Interaction in Brazil for 2025-2035 - Pereira, Roberto; Darin, Ticianne; Silveira, Milene Selbach (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
The II GranDIHC-BR is a collaborative initiative to identify Grand Research Challenges for Human-Computer Interaction (HCI) and define a research agenda for the next decade (2025-2035) in Brazil. A diverse group of researchers and practitioners identified seven critical societal and technological challenges for the country and the field: (1) New Theoretical and Methodological Approaches, (2) Ethics and Responsibility, (3) Plurality and Decoloniality, (4) Socio-Cultural Impacts, (5) Human-Data Interaction, (6) Implications of Artificial Intelligence, and (7) Interaction with Emerging Technologies. We reflect on the challenges and lessons learned from managing such a large-scale collaborative effort and identify areas for the community to address in the coming years. This initiative fosters a deeper sense of community and sets a course for a decade of impactful research and development in Brazil. This paper is presented bilingually in English and Portuguese as a testament to its situated and universal implications.